Ultrasonic Effects on Foam Formation of Fruit Juices during Bottling - Thünnesen, Julian; Gatternig, Bernhard; Delgado, Antonio (Eng, 2021)
Non-carbonated fruit juices often tend to foam over during bottling. The resulting foam height corresponds to the equilibrium of foam formation and decay. Therefore, the foam unexpectedly occupies more space in the bottle and carries parts of the juice out of the bottle, resulting in product loss under filled containers and hygienic problems in the plant. Chemical antifoams are likewise undesirable in most cases. Recent ultrasonic defoamers are effective but only capable outside the container and after the filling. In this article, a lateral ultrasonication through the bottle wall with frequencies between 42 and 168 kHz is used in-line for non-invasive foam prevention during filling. Foam formation during hot bottling of orange juice, apple juice, and currant nectar at 70 °C happens at flow rates between 124–148 mL/s. The comparably high frequencies have a particular influence on the fresh foams, where a large fraction of small resonant bubbles is still present. Foam volume reductions of up to 50% are reached in these experiments. A low power of 15 W was sufficient for changing the rise of entrained bubbles and minimizing the foam development from the start. The half-life of the remaining foam could be reduced by up to 45% from the reference case. The main observed effects were a changed rise of entrained bubbles and an increased drainage.
CRIS-Team Scopus Importer:2024-12-16
Keywords: foam drainage; foaming behavior; fruit juice; glass bottles; ultrasound application